Penerapan Pragmatik: Analisis Kebiasaan Tindak Tutur dan Kesantunan Berbahasa dalam Komunitas Mahasiswa Universitas Negeri Medan - Adelia Rahma Dani; Annisa Pohan; Dinda Barqah Sulistiorini; Syahbrina Virgi Darmawan; Afza Rifa Yusda; M.Oky Fardian Gafari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research analyzes the speech acts used by the student community at Universitas Negeri Medan in both academic and social interactions. Speech acts are the smallest components in communication that determine the meaning or intention of an utterance as conveyed by the speaker in accordance with a specific context or condition. The communication context consists of social contexts, which refer to the relationship between the speaker and the interlocutor. The purpose of this study is to identify the forms, principles, implicatures, deixis, and how various communication contexts influence the choice of speech acts and linguistic politeness. The methodology employed in this study combines methodological and theoretical approaches. The methodological approach is descriptive qualitative, while the theoretical approach applies pragmatic perspectives supported by literature review. The research methods include observation, interviews, audio recordings, transcription, and literature study by analyzing relevant sources. The findings reveal that in social interactions, students more frequently employ expressive and commissive speech acts to build and express emotions. Factors influencing this include situational context, the impact of media and technology, relationships with interlocutors, and cultural background. The study concludes that understanding speech acts is crucial for improving communication effectiveness among students in both academic and social settings. The implications of this research can be applied to the development of better communication strategies in educational environments and to enhance students’ awareness of polite and contextually appropriate language use.